Analisis Pengaruh Kemampuan Market Selectivity Timing dan Efek Dilusi Fund Flow Terhadap Return Reksadana Saham - R. Nugroho Purwantoro; Yochiko Imphiami (Jurnal Manajemen dan Usahawan Indonesia, 2020)
The objective of this study is to analyze the effects of market selectivity and market timing ability of fund managers, and also the dilution effect of fund flow from investor to the return of equity mutual funds. The result shows that the mutual funds did have market selectivity and market timing ability although unsignificant, and there are no dilution effect found from trading activity of the mutual funds investors.